Designing Freedom - Beer, Stafford (London; New York: John Wiley & Sons, 1974)
This book is a text of the six radio broadcasts given in the autumn of 1973 as the thirteenth series of Massey lectures which were established in 1961 by the Canadian broadcasting corporation to enable distinguished authorities in fields of general interest and importance to present the results of original study or research.
ne 27/04/2018
Loan
Keywords: Operations Research; Social Systems; Cybernetics